A Decorated Bronze Belt from Gargul, Iran. Issue 2 (3rd July 2019) - Cifarelli, Megan; Mollazadeh, Kazem; Binandeh, Ali
ABSTRACT: During the early first millennium BC, the southern Lake Urmia basin in northwestern Iran was in the throes of political, military and cultural upheaval. Its material culture, as exemplified by the finds at Hasanlu, Marlik and in Luristan, suggests the elite in the area were consumers of fine, locally produced metalwork. This paper discusses the discovery of an artifact that expands our understanding of the material culture of northwestern Iran during the ninth century BC: a decorated bronze belt found at Gargul, Iran. The chance discovery of this belt, which is closely related to a type known only from the most elite contexts at Hasanlu, Iran, provides a hint of the richness and complexity of the entire region. This belt demonstrates that Hasanlu was not the only regional polity wealthy and powerful enough to employ skilled artisans for the creation of sophisticated luxury goods. While the craftsmanship of this belt does not match that of exemplars from Hasanlu, it clearly evidences similarly advanced metallurgical skills, awareness of a range of contemporary and ancient iconographic traditions from the highest reaches of power in Assyria to local sites like Hasanlu, and the means and desire to combine them to aggrandise the bodies and identities of the local elite.